Pengaruh Koordinasi Terhadap Pengambilan Keputusan Pada Kantor Kecamatan Tempe Kabupaten Wajo - Eka Patmasari; Sofyan Marzuki; Sumarno Sumarno (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
This research aims (1) to analyze how well employees coordinate at the Tempe District Office, Wajo Regency; (2) To analyze how well employees make decisions at the Tempe District Office, Wajo Regency; and (3) To analyze and understand the influence of coordination on employee decision making at the Wajo Regency District Office. This research method is the associative method and quantitative method. The associative method is the method used to determine the relationship or influence between the independent variable, namely coordination, and the dependent variable, namely decision making. In addition, based on the type of data and analysis, this research uses quantitative methods. By using quantitative methods, the data obtained will be accurate according to statistical calculations. The conclusions in this research are (1) Overall the Coordination dimension (unity of action, communication, division of work, and discipline) at the Tempe District Office, Wajo Regency is in the Good category with a total score of 1715 with an average percentage of 82.06% of the ideal score ; (2) Overall the dimensions of Decision Making (understanding stage, design stage, selection stage, and implementation stage) at the Tempe District Office, Wajo Regency are in the Very Good category with a total score of 966 with an average percentage of 84.74% of the ideal score; and (3) The relationship (correlation=r) between the coordination variable and decision making at the Tempe District Office, Wajo Regency is in the strong category with a value of 0.617. Thus, this value shows that the coefficient value is positive, which means that there is a positive relationship in the sense that every time there is an increase in coordination, decision making at the Tempe District Office, Wajo Regency increases. For the regression coefficient for the coordination variable (x) with a value of 0.508, this means that if the coordination variable increases by one, then decision making at the Tempe District Office, Wajo Regency will experience an increase of 0.508. A positive value in the regression results indicates a positive influence, meaning that there is a positive relationship between the coordination variable and the decision making variable at the Tempe District Office, Wajo Regency.